ANALYSIS OF THE INDONESIAN NATIONAL TEAM'S DEFENSIVE STYLE AT THE AFC ASIAN CUP QATAR 2023 - Ramadhan Rizky Wahyu P.; Apriliyanto, Rizki; Hardovi, Bahtiar Hari (Gladi : Jurnal Ilmu Keolahragaan, 2025)
The purpose of this research is to find out the defensive style of the Indonesian national team in the AFC Asian Cup Qatar 2023 and provide coaches for recommending a defense system that suits their team. This research method uses quantitative research with a descriptive approach. The population was taken by observing all videos of the Indonesian national team's matches at the 2023 AFC Asian Cup Qatar. Based on the research, it can be concluded that the defense of the Indonesian national team is divided into three categories as follows; Through high pressing, a success percentage of 79.7% and failure of 20.3% were obtained, through middle pressing, a success percentage of 78.7% and failure of 21.3% were obtained, and low pressing was obtained a success percentage of 69.7% and failure reached 30.3%. The Indonesian national team in the AFC Asian Cup Qatar 2023 showed that high pressing is the most effective strategy for the defense system.